ANALYSIS THE QUALITY OF HIGH SCHOOL STUDENTS' ANSWERS USING SOLO TAXONOMY BASED INSTRUMENTS - Seila Agustina; Irham Ramadhani (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
Students’ understanding of fluid concepts at the senior high school level remains relatively low, as many students are able to apply formulas but still experience difficulties in connecting concepts comprehensively. This study aimed to analyze the quality of students’ responses on fluid topics based on the SOLO Taxonomy. A quantitative descriptive method was employed involving 80 eleventh-grade students of SMA Negeri 1 Medan selected through cluster sampling. The research instrument was a SOLO Taxonomy-based diagnostic test consisting of 12 valid items. Data were analyzed by classifying students’ responses into SOLO levels and determining the distribution of understanding levels achieved. The results showed that the instrument had good reliability with a coefficient of 0.887, discrimination indices predominantly in the very good category, and varied levels of difficulty. The analysis revealed that the multistructural level was the most dominant level of understanding achieved by students. This finding indicates that most students were able to understand several relevant concepts but had not yet integrated them into a coherent conceptual framework. Consequently, students’ understanding tended to reflect surface learning rather than deep learning. Therefore, instructional strategies that promote higher levels of conceptual understanding are needed. ABSTRAK Pemahaman konsep fluida pada siswa sekolah menengah atas masih tergolong rendah karena banyak siswa mampu menggunakan rumus, tetapi mengalami kesulitan dalam menghubungkan konsep secara menyeluruh. Penelitian ini bertujuan untuk menganalisis kualitas jawaban siswa pada materi fluida berdasarkan Taksonomi SOLO. Penelitian menggunakan metode deskriptif kuantitatif dengan melibatkan 80 siswa kelas XI SMA Negeri 1 Medan yang dipilih melalui teknik cluster sampling. Instrumen penelitian berupa tes diagnostik berbasis Taksonomi SOLO yang terdiri atas 12 butir soal valid. Data dianalisis dengan mengelompokkan jawaban siswa ke dalam level SOLO dan menghitung distribusi tingkat pemahaman yang dicapai. Hasil penelitian menunjukkan bahwa instrumen memiliki reliabilitas yang baik dengan koefisien sebesar 0,887, daya pembeda yang didominasi kategori sangat baik, serta tingkat kesukaran yang bervariasi. Analisis jawaban siswa menunjukkan bahwa level multistruktural merupakan tingkat pemahaman yang paling dominan. Temuan ini menunjukkan bahwa sebagian besar siswa telah mampu memahami beberapa konsep yang relevan, tetapi belum mampu mengintegrasikannya secara utuh sehingga pemahaman yang dimiliki masih cenderung berada pada tahap surface learning dibandingkan deep learning. Oleh karena itu, diperlukan strategi pembelajaran yang dapat mendorong siswa mencapai tingkat pemahaman yang lebih tinggi.